The Syrian wars - Grainger, John D., 1939- (Mnemosyne, bibliotheca classica Batava. Supplementum, 2010)
This book examines the causes and courses of the series of wars in the Hellenistic period fought between the kingdom of the Seleukids and the Ptolemies over possession of Syria. This is a subject always mentioned by historians of the period in a glancing or abbreviated way, but which is actually wholly central to the development of both kingdoms and of the period as a whole. Other than relatively brief summaries no serious account has ever been produced. This extended consideration will bring to the centre of research on the Hellinistic period this long sequence of wars. Arguably they were the.